Ask a New Question
Search
Simplify 5(7x-2)-14x+4.
1 answer
Expanding the expression gives 35x - 10 - 14x + 4.
Combining like terms, we get 21x - 6.
So, the simplified expression is 21x - 6.
Ask a New Question
or
answer this question
.
Similar Questions
simplifying square roots
1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
3 answers
Simplify 8a − 2a.
Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
4 answers
simplifying square roots
1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
3 answers
1. Simplify 5^-1(3^-2)
A. 45 B. 1/45 C. 15^-3 D. 15^2 2. Simplify (3xy^3)^2(xy)^6 A. 9x^8y^12 B. 3x^8y^12 C. 2x^3y^12 D. 9x^8y^9
7 answers
more similar questions